2014
DOI: 10.1007/s00415-014-7332-9
|View full text |Cite
|
Sign up to set email alerts
|

Neurological abnormalities predict disability: the LADIS (Leukoaraiosis And DISability) study

Abstract: To investigate the role of neurological abnormalities and magnetic resonance imaging (MRI) lesions in predicting global functional decline in a cohort of initially independent-living elderly subjects. The Leukoaraiosis And DISability (LADIS) Study, involving 11 European centres, was primarily aimed at evaluating age-related white matter changes (ARWMC) as an independent predictor of the transition to disability (according to Instrumental Activities of Daily Living scale) or death in independent elderly subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
0
14
1
Order By: Relevance
“…In the Leukoariosis and Disability study (LADIS) (n = 639, mean age 74) the association of SCVD with gait speed was examined cross-sectionally and prospectively in a predominantly European population with similar findings to ours. 13 Unlike LADIS however we found no association of silent infarcts with gait speed. Investigators in the Tasmanian Study of Cognition and Gait (n = 395) also found a cross-sectional association of SBI and cardiovascular disease risk factors, with gait speed.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…In the Leukoariosis and Disability study (LADIS) (n = 639, mean age 74) the association of SCVD with gait speed was examined cross-sectionally and prospectively in a predominantly European population with similar findings to ours. 13 Unlike LADIS however we found no association of silent infarcts with gait speed. Investigators in the Tasmanian Study of Cognition and Gait (n = 395) also found a cross-sectional association of SBI and cardiovascular disease risk factors, with gait speed.…”
Section: Discussioncontrasting
confidence: 73%
“…The mechanisms by which subclinical cerebrovascular injury leads to impaired mobility is unclear though a potential explanation is disruption of cortical to subcortical connectivity, leading to impairment in cerebral pathways underlying gait. 8,12,13 Due to the high public health burden associated with mobility impairment, further research is required to identify modifiable risk factors across a range of different populations.…”
Section: Introductionmentioning
confidence: 99%
“…; Poggesi et al . ). There is a higher incidence of vascular risk factors, primarily hypertension, in those with the progressive dementia.…”
Section: Biomarkers In Binswanger's Diseasementioning
confidence: 97%
“…In a second substudy, the role of neurological abnormalities and MRI lesions in predicting global functional decline was explored . In addition to WMC grading, MRI assessment included count of lacunar and non‐lacunar infarcts and global atrophy rating.…”
Section: Wmc and Neurological Signsmentioning
confidence: 99%